2014
DOI: 10.4212/cjhp.v67i2.1343
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Automated Dispensing Devices: Systematic Review of Clinical and Economic Impacts in Hospitals

Abstract: ADDs have limited potential to decrease medication errors and increase efficiencies, but their impact is highly institution-specific, and use of this technology requires proper integration into an institution's medication distribution process. Before deploying this technology, it is recommended that Canadian hospitals carefully examine their current systems and the benefits they hope to gain with the changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 12 publications
1
50
0
6
Order By: Relevance
“…A further factor for decision-makers to consider before implementing new initiatives is the cost of the intervention. Only a few studies have evaluated the cost differences between different alternatives for improvement of patient safety in relation to medication errors 9 24. Such economic evaluations are highly relevant to decision-making when scarce resources within the healthcare system are being prioritised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further factor for decision-makers to consider before implementing new initiatives is the cost of the intervention. Only a few studies have evaluated the cost differences between different alternatives for improvement of patient safety in relation to medication errors 9 24. Such economic evaluations are highly relevant to decision-making when scarce resources within the healthcare system are being prioritised.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of automated drug dispensing has been tested previously, but with inconsistent results. Some studies have found a reduction in the number of medication errors,7 8 although a recent review by Tsao et al 9 concluded that decentralised automated dispensing devices had limited potential to reduce medication errors, and that the impact of such devices is highly institution-specific. This highlights the need for testing automated dispensing systems in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Tsao et al (2014) mendapatkan bahwa automated dispensing device memiliki potensi menurunkan medication error dan meningkatkan efisiensi yang terbatas. Potensi tersebut sangat tergantung pada institusi yang menerapkan dan seberapa baik diintegrasikan dengan proses distribusi obat.…”
Section: Pendahuluanunclassified
“…Automated drug delivery systems, popularly known as electronic dispensers for drugs and materials, are a promise of improved patient care, reduced medication errors, decreased costs, and a closer approximation of the pharmacist to direct patient care. [1][2][3] According to a technical opinion issued by the Health Technology Assessment Institute, electronic dispensaries can be defined as dispensing devices through an interface between the prescription and the equipment and can be classified as centralized (when located within the pharmacy service) or decentralized (if they are deployed in inpatient units). These systems allow the maintenance of decentralized stocks, however, controlled by the pharmacy staff.…”
Section: Introductionmentioning
confidence: 99%